End-to-end QoS provisioning in 4G with mobile hotspots. - Lera, A. (IEEE Network : the magazine of global information exchange)
The novel concept of mobile hotspots, characterized by a group of wireless users equipped with wireless LAN cards, moving as a whole and requiring Internet connectivity, is gaining the interest of the telecommunications research community. This article intends to contribute to this research topic by proposing alternative solutions for the deployment of a mobile gateway device offering 3G connectivity to the group of WLAN users while they are moving. This is a decisive aspect of the 3G migration to 4G networks. The proposed solutions allow for two-hop wireless paths between WLAN and 3G systems, and performing control over-high layer issues, specifically focusing on end-to-end QoS provisioning. The pros and cons of envisaged design solutions are addressed and their relevance justified considering purposes, target users, and applications.